Challenges related to the implementation of the CCMDD programme in Sekhukhune clinics - Ragosebo P. Sekopa; Robert T. Netangaheni (AOSIS, 2024)
Background: Implementation of the central chronic medicines dispensing and distribution (CCMDD) programme in most of Sekhukhune primary health care (PHC) has been challenging. This raised questions as to reasons for the CCMDD programme and its good intentions and benefits eventually creating challenges in the Sekhukhune district PHC facilities. Aim: This study aims to describe the challenges related to the implementation of the CCMDD programme in Sekhukhune district clinics. Method: The qualitative research approach and its explorative and descriptive research designs were used in this study. Data were acquired through one-on-one semi-structured interviews and then analysed thematically. Results: Findings of the study revealed that shortage of staff, lack of communication, defaulters, negative impact of the CCMDD programme and lack of training as challenges to the implementation of the CCMDD programme in Sekhukhune district clinics. Conclusion: Sekhukhune public clinics have challenges concerning the implementation of the CCMDD programme; therefore, it is very crucial to provide proper training about the programme to all PHC facility staff members to improve the CCMDD implementation. Contribution: The study would provide suggestions to implement the CCMDD programme by correcting the process of enrolling clients, the methods of packaging and dispensing the medications, sending SMSs, as well as delivery to the pick-up points.